Dependability of Networked Computer-based Systems - Verma, Ajit Kumar; Ajit, Srividya; Kumar, Manoj; SpringerLink (Online service) (London : Springer London, 2011)
The measurement of dependability attributes on real systems is a very time-consuming and costly affair, making analytical or simulation modeling the only viable solutions. Dependability of Networked Computer-based Systems explores reliability, availability and safety modeling of networked computer-based systems used in life-critical applications such as avionics, nuclear power plants, automobiles and chemical process industries. Dependability of Networked Computer-based Systems gives an overview of basic dependability modeling concepts and addresses new challenges in dependability modeling of networked computer-based systems, as well as new trends, their capabilities and limitations. It covers a variety of dependability modeling methods: stochastic processes, Markov and semi-Markov models, response-time distribution, stochastic Petri-net-based modeling formalisms, and Monte Carlo simulation models. Dependability of Networked Computer-based Systems provides students and researchers with a detailed overview of dependability models and analysis techniques. Practicing engineers will also find this text a useful guide to decision-making based on system dependability at the design, operation and maintenance stages.
1. Introduction -- 2. Probability Theory -- 3. Stochastic Processes and Models -- 4. Dependability Models of Computer-based Systems -- 5 Network Technologies for Real-time systems -- 6. Response-time Models and Timeliness Hazard Rate -- 7. Dependability of Networked Computer-based Systems.
Keywords: Engineering; Operating systems (Computers).; Computer system performance; Computer science; System safety; Telecommunication; Engineering; Quality Control, Reliability, Safety and Risk; Performance and Reliability; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Communications Engineering, Networks; System Performance and Evaluation; Models and Principles